With US or against US? European trends in American perspective - Jabko, Nicolas; Parsons, Craig, 1970-; Oxford eBooks; European Union Studies Association (Oxford : Oxford University Press, 2005)
This volume provides new insights on both the recent evolution of the EU and its future developmental trajectory, and maps European trends against American policies and institutions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: European Union countries -- Foreign relations -- United States; United States -- Foreign relations -- European Union countries; Electronic books